1995
DOI: 10.1029/94wr02565
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “Falling Head Ponded Infiltration” by J. R. Philip

Abstract: An exact solution for falling head infiltration into a Green and Ampt [1911] soil was presented by Philip [1992]. Philip's result, first published in English in the widely known book by Polubarinova-Kochina [1962, p. 490], is a special case of a previously published infiltration formula due to Parlange et al. [1985]. The latter holds for arbitrary, time-dependent ponded conditions at the soil surface and does not require that the soil water diffusivity be proportional to a delta function. In particular, the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
7
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 7 publications
4
7
0
Order By: Relevance
“…From the analytically solvable model, infiltration coefficients were constructed unambiguously from a complicated but explicit recurrence relation. Our recent results support the ideas of Parlange [1972, 1975] and Barry et al [1995], since along the curves in the two‐parameter space that have a limiting delta‐function diffusivity, the second infiltration coefficient is not uniquely determined, but it has a limiting value that depends on the form of K(θ) . Or more directly, it depends on the form of the function that maps the Buckingham soil‐water potential Ψ to K .…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…From the analytically solvable model, infiltration coefficients were constructed unambiguously from a complicated but explicit recurrence relation. Our recent results support the ideas of Parlange [1972, 1975] and Barry et al [1995], since along the curves in the two‐parameter space that have a limiting delta‐function diffusivity, the second infiltration coefficient is not uniquely determined, but it has a limiting value that depends on the form of K(θ) . Or more directly, it depends on the form of the function that maps the Buckingham soil‐water potential Ψ to K .…”
Section: Introductionsupporting
confidence: 78%
“…Unfortunately, this model predicts S 1 to be 2Ks/3 , which is approximately double that calculated numerically from models with strongly increasing but more realistic continuous functions for D(θ) and K(θ) [ Philip , 1990; Barry et al , 1995; Ross et al , 1996] or inferred from infiltration data [ Talsma , 1969; Youngs , 1995]. In the aftermath of the papers by Philip [1992a, 1992b, 1993] three comments debating delta‐function soils were published with replies from John Philip [ Barry et al , 1994, 1995, 1996; Philip , 1994, 1995, 1996]. From Philip [1995]: “The topic of ‘delta‐function’ soils and their relation to the Green–Ampt model seems to remain in confusion.” More recently, Barry et al [2010] have pointed out that setting a soil's “effective conductivity” to be half the saturated hydraulic conductivity within a Green–Ampt infiltration analysis [ Mailapalli et al , 2009; Rawls et al , 1993] has the effect of halving the value of S 1 .…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Material in the paper follows directly from previous work by the same author [Philip, 1992a, b]. We have commented on these papers [Barry et al, 1994[Barry et al, , 1995, and some of the same remarks are relevant to the theory presented by Philip [1993, p. …”
Section: Introductionmentioning
confidence: 94%
“…Parlange et al (1982) provided a three-parameter infiltration equation that reduces to the Green-Ampt and Talsma-Parlange models as limiting cases. It has been shown that infiltration into soil is usually closer to the Talsma-Parlange model than the Green-Ampt model (e.g., Fuentes et al, 1992;Barry et al, 1995c;Ross et al, 1996;Clausnitzer et al, 1998).…”
mentioning
confidence: 99%